Mom’s Knowledge About Preventing Dental Caries In Preschool Children In Nusantar Tk, Simalungun Regency In 2021 - Lilis Novitarum; Imelda Sirait; Laila Aristina (Jurnal EduHealth, 2022)
Mother who is the closest person to the child in health care has a significant influence on the attitude and behavior of the child. Kindergarten age children generally do not know and have not been able to maintain the health of their oral cavity, so it is the parents’ responsibility to educate them properly. The purpose of this study was to determine the mother’s knowledge about the prevention of dental caries in preschool children at Nusantara Kindergarten in 2021. This research design uses a descriptive survey with the sampling technique of a total sampling of 35 respondents in Tk Nusantara Tanah Java. The instrument used in data collection is a questionnaire. Analysis of the data shows the results of the description of the knowledge of mothers in Tk Nusantara Tanah Jawa obtained data that the majority of respondents have good knowledge as many as 33 people (91.7%), The researcher recommends that further researchers should conduct similar researchers, it is hoped that they will examine the relationship between knowledge level and dental health maintenance behavior in elementary school children. For further researchers, it is also recommended to choose a total sampling technique according to the conditions and characteristics of the population.